A redox-activatable biopolymer-based micelle for sequentially enhanced mitochondria-targeted photodynamic therapy and hypoxia-dependent chemotherapy. Issue 69 (28th July 2020) - Li, Yanan; Sutrisno, Linawati; Hou, Yanhua; Fei, Yang; Xue, Chengcheng; Hu, Yan; Li, Menghuan; Luo, Zhong
Abstract : This work reports a biopolymer-based micellar nanoplatform with redox-sensitivity for sequentially enhanced mitochondria-targeted photodynamic therapy and hypoxia-amplified chemotherapy against CD44-positive tumors. Abstract : A tumor redox-activatable micellar nanoplatform based on the naturally occurring biomacromolecule hyaluronic acid (HA) was developed for complementary photodynamic/chemotherapy against CD44-positive tumors. Here HA was first conjugated with l -carnitine (Lc)-modified zinc phthalocyanine (ZnPc) via disulfide linkage and then co-assembled with tirapazamine (TPZ) to afford the physiologically stable micellar nanostructure. The mitochondria-targeted photodynamic activity of ZnPc-Lc could efficiently activate the mitochondrial apoptosis cascade and deplete the oxygen in the tumor intracellular environment to amplify the hypoxia-dependent cytotoxic effect of TPZ.